Peran Gaya Rambut dalam Mencegah atau Memperburuk Masalah Rambut Seperti Ketombe dan Rambut Rontok - Ifa Nurhayati; Anik Maghfiroh; Friska Kirana Andieta Rinjani; Thalla Ghaitsa’ Anwar; Era Patrika Sakti (An-Najat, 2025)
Hair problems such as dandruff and hair loss are often influenced by various factors, including the hairstyle chosen. This study aims to analyze the role of hairstyle in preventing or optimizing these conditions. The methods used were observational studies and questionnaires involving respondents with various hair styling habits. The results showed that overly tight hairstyles, excessive use of hot tools, and suboptimal scalp hygiene can increase the risk of dandruff and hair loss. Conversely, looser hairstyles, good scalp care, and the selection of appropriate products can help maintain healthy hair. These findings emphasize the importance of education regarding the selection of hairstyles that are not only aesthetic but also consider hair and scalp health. The implications of this study can be a reference for beauty practitioners and the public in choosing hairstyles that are safer for hair health.